Respuesta :

93. [tex]g(n) = n - 4[/tex]
[tex]f(n) = 2n^2 - 5n[/tex]

then [tex]g(n) +f(n) = (n-4) + (2n^2 - 5n)[/tex]
                                [tex]= n - 4 + 2n^2 - 5n[/tex]
                                [tex]= 2n^2 -5n + n - 4[/tex]
                                [tex]= 2n^2 - 4n -4[/tex]


95. [tex]f(n) = -n+3[/tex]
      [tex]g(n) = n^3 + 3n[/tex]
Then [tex]f(n) . g(n) = (-n+3) . (n^3 + 3n)[/tex]
                                 [tex]= -n^4 + 3n^3 - 3n^2 + 9n [/tex]
 

97. [tex]f(x) = 3x+1[/tex]
[tex]g(x) = 2x[/tex]
For finding f(g(x)) we will plugin value of g(x) in place of x in f(x).
[tex]f(g(x)) = 3*(2x) + 1[/tex]
                  [tex]= 6x + 1[/tex]


99. [tex]f(n) = n - 3[/tex]
[tex]g(n) = 2n^2 - 3n[/tex]

[tex]g(-7) = 2*(-7)^2 - 3 * (-7) = 2* 49 + 21 = 98 + 21 = 119[/tex]
[tex]f(g(-7)) = 119 - 3 = 116[/tex]

Answer:

97.

For finding f(g(x)) we will plugin value of g(x) in place of x in f(x).

                 

99.

Step-by-step explanation:

ACCESS MORE